2021
DOI: 10.1590/1678-4685-gmb-2020-0470
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic diversity and diversification processes in three cis-Andean Rhamdia species (Siluriformes: Heptapteridae) revealed by DNA barcoding

Abstract: The wide distribution of the Neotropical freshwater catfish Rhamdia offers an excellent opportunity to investigate the historical processes responsible for modeling South America's hydrogeological structure. We used sequences from cis-Andean and Mesoamerican Rhamdia species to reconstruct and estimate divergence times among cis-Andean lineages, correlating the results with known geological events. Species delimitation methods based on distance (DNA barcoding and BIN) and coalescence (GMYC) approaches identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The distinction of these two species is supported by the studies by Perdices et al (2002), in which the mtDNA analyses place the trans-Andean ‘ Rhamdia quelen ’ of Central America in a different clade from the typical cis-Andean R. quelen of South America (Hernández et al , 2015). Rhamdia quelen found in South America is known to be a complex of cryptic species, containing at least seven allopatric molecular operational taxonomic units associated to different hydrological basins (Ribolli et al , 2021), which could become separate species if shown to be independent evolutionary lineages.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction of these two species is supported by the studies by Perdices et al (2002), in which the mtDNA analyses place the trans-Andean ‘ Rhamdia quelen ’ of Central America in a different clade from the typical cis-Andean R. quelen of South America (Hernández et al , 2015). Rhamdia quelen found in South America is known to be a complex of cryptic species, containing at least seven allopatric molecular operational taxonomic units associated to different hydrological basins (Ribolli et al , 2021), which could become separate species if shown to be independent evolutionary lineages.…”
Section: Introductionmentioning
confidence: 99%